Adoption of Improved Sericultural Technologies among Farmers of Mizoram State - J., Parameswaranaik; , Lalhriatkima; G.R., Manjunatha; V., Sivaprasad (Journal of Agricultural Extension Management, 2020)
The state of Mizoram is endowed with a very pleasant and conducive climatic condition for silkworm rearing along with fertile soil and abundant rainfall giving a favourable atmosphere for sericulture activities. Mulberry silkworm Bombyxmori is an inhabitant of the State. Mulberry is cultivated in 4094 hectares in approximately 175 villages and Mizoram occupies the third place in producing mulberry raw silk (75 MT) among the northeastern states of India. The gap between the potential and actual yield in mulberry sericulture is very wide. One major factor is attributed to be ignorance and non-adoption of improved recommended technologies. The productivity depends on the extent to which farmers adopt new technologies. With this background the present study was conducted to assess the adoption of improved technologies, with 60 sericulture farmers of three districts in Mizoram. The findings reveal that 100 percent of the respondents adopted the tray rearing method and plastic collapsible mountage and have a separate rearing house. Low level of adoption was found in integrated pest management (60 % partial and 40 % no adoption) and integrated nutrient management (75% partial adoption). Hence there is a scope for the extension agency to conduct training programs on integrated pest management and integrated nutrient management in the study area.